Energy Policy : Setting the Stage for the Current Debate. (U.S. Congressional Research., 2001)
Discusses the background of and analyzes U.S. energy policy, focusing on the period 1999 to 2001. Presents an energy policy schematic, examines what is different about the current policy debate relating to petroleum and natural gas, electricity restructuring, and other issues, and reviews energy legislation in the 107th Congress.